Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Chapter 6 - Review Exercises - Page 292: 54



Work Step by Step

Subtract $4\pi$ to both sides: $-4\cot^{-1}{(x)}=-3\pi$ Divide $-4$ to both sides: $\cot^{-1}{(x)}=\frac{-3\pi}{-4} \\\cot^{-1}{(x)}=\frac{3\pi}{4}$ RECALL: $\cot^{-1}{(x)} = \theta \longrightarrow \cot{\theta} = x$ Use the rule above to obtain: $\cot^{-1}{(x)} = \frac{3\pi}{4} \\\cot{(\frac{3\pi}{4})}=x \\-1=x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.